Micro-Tomographic Atlas of the Mouse Skeleton - Bab, Itai A.; Hajbi-Yonissi, Carmit; Gabet, Yankel; Müller, Ralph (Springer US : Imprint: Springer, 2007)
Micro-Tomographic Atlas of the Mouse Skeleton Professor Itai Bab, Chief, Bone Laboratory, The Hebrew University of Jerusalem, Jerusalem, Israel Professor Ralph Müller, Director, Center for Bioengineering Research and Education, ETH Zürich, Switzerland Micro-Tomographic Atlas of the Mouse Skeleton serves as an essential guide containing unique systematic description of all calcified components of the mouse. This detailed atlas fulfils an emerging need for high resolution anatomical details as mice become a standard laboratory animal in skeletal research and the use of m CT technology is rapidly increasing as a key analytical tool in the study of bone. Key Features: Includes over 200 high resolution, two- and three dimensional m CT images of the exterior and interiors of all bones and joints Offers the spatial relationship of individual bones within complex skeletal units (e.g., skull, thorax, pelvis, extremities). All images are accompanied by detailed explanatory text that highlights special features and newly reported structures. Available for the first time in the Atlas: Detailed information on the micro-anatomy of the murine skeleton essential for the design of experiments and interpretation of results Comparative analyses on m CT-based morphometric parameters at the whole bone, cortical and trabecular levels including: Age differences (4-40 weeks) Gender differences Differences between main mouse strains (C57Bl/6J, SJL, C3H) Micro-Tomographic Atlas of the Mouse Skeleton offers a practical, comprehensive desk reference for all scientists and students interested in skeletal biology.